Toxic stress on a pediatric population during the COVID-19 pandemic - Anna Beatriz Galheiro Silvério; Denise Leal de Souza; Gabriela de Sio Puetter Kuzma; Gabriela Storithont Mudri; Isabelle Beatriz Freccia Nagel; Julia Concer da Silva; Leonardo Cecconello; Raissa Peres de Oliveira; Raissa Wurth Marchinhacki; Samantha Nagasako Soejima (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: The aim of this study was to analyze the impact of social isolation as a result of the coronavirus-19 disease (COVID-19) pandemic in children and adolescents aged 0-17 years in Southern Brazil. Methods: This is a cross-sectional study in which 542 questionnaires answered by parents or legal guardians of children and adolescents aged 0-17 years residing in the Brazilian South region, through Google Forms®. Questionnaires answered incompletely or from children outside the stipulated age group and from other regions of the country were excluded from the research. The collected data were organized into descriptive and association tables containing absolute and relative frequencies, medians, averages, standard deviations, quartile deviations, average, and proportion estimates in the form of 95% confidence intervals and the result of the chi-square test of independence. Data analysis was fulfilled with the application aid of Microsoft Excel 2016 and Epi Info version 7.2.1.0 of 01/27/2017. Statistically significant associations were considered when p<0.05. Results: There was an increase in the perception of nervousness (62.7%), anxiety (67.7%), and sadness (51.3%) in children and adolescents during the pandemic period. This study evidenced a high prevalence of screens overuse (50.9%) and sedentary lifestyle (39.1%) in this age group during the period. Furthermore, the occurrence of regressive behaviors occurred more frequently in the age group of 3-6 years (57.1%) and between 7 and 10 years (44.6%). Conclusions: It is inferred from this study that one of the implications resulting from the pandemic period is the increase of toxic stress in the pediatric population.